Activation level as a mediator between behavioral activation, sex, and depression among treatment-seeking smokers. (March 2021) - Weidberg, Sara; González-Roz, Alba; García-Fernández, Gloria; Secades-Villa, Roberto
Highlights: We tested sex and BA effects on depression with activation level as a mediator. There was no effect of treatment condition, sex or their interaction on depression. BA's effect on depressive symptoms was mediated by activation levels only in males. Tailoring interventions by sex when treating smokers with depression is encouraged. Abstract: Introduction: Behavioral activation (BA) has gained interest when combined with tobacco interventions as it relates to improved depression and cessation rates. However, no prior efforts have examined mediators of BA effectiveness and sex-dependent effects. This secondary analysis assesses the main and interactive effects of sex and type of smoking cessation intervention [a cognitive behavioral treatment (CBT) only, or CBT + BA] on depressive symptoms among treatment-seeking patients with depression. It also examines the activation level as a mediator between BA, BA by sex, and depression. Method: 120 smokers were assigned to an 8-week CBT or to CBT + BA. They completed the Beck Depression Inventory-II (BDI-II) and the Behavioral Activation for Depression scale-short-form (BADS-SF). A two-way ANOVA assessed the effects of sex and treatment condition on participants' BDI-II scores. A moderated mediational analysis tested whether the indirect effect of treatment condition on BDI-II through BADS-SF differed by sex. Results: After controlling for end-of-treatment smoking status and baseline BDI-II, there were no significant effects of treatment condition, sex, and their interaction on end-of-treatment BDI-II. Being a male was indirectly associated with higher BDI-II scores through lower BADS-SF score (point estimate = −3.440; SE  = 1.637; BC 95% CI [−7.105, −0.749]). This effect was not found for women. Conclusions: There is a need to tailor interventions by sex when treating smokers with depression. It is recommended to assess symptoms such as mental rumination or self-consciousness, which tend to be more pronounced in women.